Combating Corruption Relates Money Laundering Activities in Indonesia: A Hope and Reality - Sigit Handoyo (Universitas Islam Indonesia, 2008)
Corruption in Indonesia has become a culture and systemic so that it could not be eradicated in the short period of time. As corruption is closely related to money laundering activities, it is not impossible that combating corruption also means combating money laun-dering activities. PPATK (Pusat Pengkajian dan Analisis Transaksi Keuangan) as the Indone-sia’s FIU (Financial Intelligence Unit) has hard works to reveal those money laundering and corruptions activities. Beside its obstacles, PPATK also has challenges in the future. This arti-cle presents a study which discusses Indonesian cases in relations to money laundering and corruption, as well as the challenges that will be faced by PPATK as the Financial Intelli-gence Unit in combating money laundering activities.Keywords: corruption, money laundering, PPATK, FIU